A simple method for normalization of DNA extraction to improve the quantitative detection of soil‐borne plant pathogenic oomycetes by real‐time PCR. (1st August 2015) - Li, M.; Ishiguro, Y.; Kageyama, K.; Zhu, Z.
Abstract: Most of the current research into the quantification of soil‐borne pathogenic oomycetes lacks determination of DNA extraction efficiency, probably leading to an incorrect estimation of DNA quantity. In this study, we developed a convenient method by using a 100 bp artificially synthesized DNA sequence derived from the mitochondrion NADH dehydrogenase subunit 2 gene of Thunnus thynnus as a control to determine the DNA extraction efficiency. The control DNA was added to soils and then co‐extracted along with soil genomic DNA. DNA extraction efficiency was determined by the control DNA. Two different DNA extraction methods were compared and evaluated using different types of soils, and the commercial kit was proved to give more consistent results. We used the control DNA combined with real‐time PCR to quantify the oomycete DNAs from 12 naturally infested soils. Detectable target DNA concentrations were three to five times higher after normalization. Our tests also showed that the extraction efficiencies varied on a sample‐to‐sample basis and were <50%. Therefore, the method introduced here is simple and useful for the accurate quantification of soil‐borne pathogenic oomycetes. Significance and Impact of the Study: Oomycetes include many important plant pathogens. Accurate quantification of these pathogens is essential in the management of diseases. This study reports an easy method utilizing an external DNA control for the normalization of DNA extraction by real‐time PCR. By combining two different efficient soil DNA extraction methods, the developed quantification method dramatically improved the results. This study also proves that the developed normalization method is necessary and useful for the accurate quantification of soil‐borne plant pathogenic oomycetes.